ENGAGING STUDENTS IN A FLIPPED CLASSROOM INSTRUCTION: JUNIOR HIGH SCHOOL GRAMMAR PROGRAM - Yanto, Elih Sutisna; Triyani, Ghyarlina; Pravitasari, Hikmah (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2020)
The importance of grammar pedagogy in learning and teaching of foreign language has been the focus of discussion for many years which has resulted in a variety of views on grammar and grammar teaching and different teaching approach as well depend on various perspectives and contexts of language learning. The present study reports students? perception on flipped classroom mode in learning English grammar. Drawing on classroom action research through reflective journal, photo elicitation and interviews data. Qualitative findings show that: All of the students enjoyed watching the video materials and had an interest in using them for learning grammar; (2) the use of the flipped classroom mode in learning grammar made students? independent and active in learning grammar; (3) flipped classroom engaged them in learning grammar in different discourse contexts; (4) flipped classroom mode motivated students in learning grammar. The findings of this study may be useful to other researchers who are interested in EFL teaching innovation or teachers who seek effective grammar teaching method.